Antibiotic-Lock Therapy in Pediatric Oncology Patients - Vanzo, Carolina; Gomila, Andres; Garnero, Analia; Bertoni, Liliana; Glatstein, Eduardo (Journal of Pediatric Infectious Diseases, 2015)
The use of long-term central venous catheters (CVCs) has increased over the past decade. There is, however, a risk of complications associated with the use of these catheters. Catheter-related bloodstream infection (CRBSI) is a common complication with a mortality rate that can be in excess of 25%. Antibiotic-lock therapy consists of filling the catheter lumen with antibiotics and allows them to dwell for a period of time, to rid the lumen from the organisms that are there and allowing the life of the catheter to be extended. The objective of this study is to evaluate the treatment of uncomplicated long-term CRBSI using lock therapy associated with systemic antibiotics among a hematology-oncology pediatric population. This is a noncomparative retrospective and descriptive cohort study. CRBSIs in patients with long-term CVCs who were treated with antibiotic-lock therapy and systemic antibiotics in oncology ward at Hospital de Niños de Córdoba between January 2005 and December 2011 were analyzed. A total of 174 noncomplicated CRBSIs were identified during this period. A total of 123 uncomplicated CRBSIs occurred in 90 patients; all of them were treated with both systemic and lock therapy. The CRBSI rate observed in 7 years was 0.57 episodes per 1000 days/catheter. Out of the 90 patients, 68 (75.56%) had acute lymphoblastic leukemia. A total of 118 episodes were monomicrobial. Gram-negative bacilli accounted for 76/123 (59%). All Klebsiella spp and Escherichia coli responded to conservative treatment. Total therapeutic success rate was achieved in 87.89%. This study suggests that antibiotic-lock therapy along with systemic therapy is an effective and reasonable alternative for the treatment of uncomplicated long-term CRBSIs in children with oncologic diseases.
Keywords: Argentina; bacteremia; catheter-related infection; pediatric oncology